International trade and economic convergence: the credit channel - Lane, Philip R. (2001)
In this paper, we examine a particular mechanism by which international trade accelerates economic convergence. We develop a model of growth under credit constraints in which international trade expands access to credit. We show in numerical simulations that reasonable values for openness generate convergence rates that match well the empirical estimates. We econometrically investigate a key prediction of the model - that more open economies exhibit greater debt to output ratios - and find substantial support in the data for this claim. This remains true even when we control for a host of additional factors and conduct robustness checks. - Reproduced
Keywords: Economic growth; International trade